Hubungan Jenis Kelamin dan Lama Sakit dengan Kejadian Depresi Pada Lansia Penderita Hipertensi - Yuniartika, Wachidah; Bima Murti, Tiara (Universitas Muhammadiyah Magelang, 2020)
Decreasing and changing physical conditions, the change in mental status as depression that often ignored, and diseases that often appear like hypertension are commonly found in the elderly, and it is a health problem that requires special attention because it will affect all aspects of life in the elderly. The purpose of this study was to determine the relationship between sex and duration of illness with the level of depression in the elderly with hypertension. The method used is descriptive quantitative with cross sectional approach. The study population was all elderly with hypertension at the Penumping Public Health Center with a sample of 54 people taken by accidental sampling. Data was collected using a research instrument in the form of a Geriatric Depression Scale (GDS) questionnaire and analyzed using a correlative test that is a Kendall tau analysis. Correlative test results between sex and depression level showed a correlation value of 0.294 with p-value (p) = 0.028, which means there is a significant relationship between sex and depression level. Correlative test between the duration of hypertension and the level of depression showed a correlation value of 0.382 with p-value (p) = 0.004, which means there is a significant relationship between the duration of hypertension and the level of depression. Discussion : The occurrence of the degeneration process in the elderly can cause physical changes and changes in the social environment such as a low economy, loss of family members, inability to fill roles in society and risk of disease. Female sex is the highest proportion and high life expectancy compared to men, so hypertension sufferers mostly occur in elderly women. Anxiety in elderly people with hypertension is caused due to the tendency to take a relatively long treatment, the risk of complications and can shorten life. The conclusion is that there is a relationship between sex and duration of illness and the level of depression in the elderly with hypertension.